The effect of multidirectional skipping on lay-up ability - Maharani Sanjaya; Iyakrus Iyakrus; Soleh Solahuddin; Wahyu Indra Bayu (Jurnal Maenpo : Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi, 2022)
This study aims to determine the effect of jumping rope exercise on the results of the lay-up shoot ability of basketball players at Club Tunas Academy Lahat. This study uses an experimental method with Quasi Experiment Design. This research is quantitative research that uses the research design method "One Group Pretest - Posttest Design. The sample used is 30 players consisting of 15 male players and 15 female players. There are two assessments in this study, namely the player's basketball lay-up shooting ability and the results of the basketball lay-up shoot ability. The analysis technique uses the "t-test" method. After doing the exercises and doing the posttest, there was an average increase of 7.73 for the ability to move the lay-up shoot for basketball and 2.47 for the average increase in the lay-up shoot ability for basketball. As well as the results of the hypothesis for the ability to shoot basketball lay ups, the value of tcount is greater than ttable, which is 21.376 > 1.70, and so is the hypothesis that the results of the basketball lay-up shoot ability are 17.409 > 1.70 then Ha is accepted and Ho is rejected, p. This shows that the jump rope training method influences the results of the lay-up shoot ability of basketball. The implication of this research is that jumping rope exercises can be used in lay-up shoots in basketball games.Key words: skipping, lay-up, basketball.